2020
DOI: 10.3389/fphys.2020.00620
|View full text |Cite
|
Sign up to set email alerts
|

CD5L, Macrophage Apoptosis Inhibitor, Was Identified in Epicardial Fat-Secretome and Regulated by Isoproterenol From Patients With Heart Failure

Abstract: Objectives: Neurohormonal dysfunction, which can regulate epicardial fat activity, is one of the main promoters of atrial fibrillation (AF) in patients with heart failure (HF). Our aim was to study the epicardial fat mediators for AF in patients with HF and its catecholaminergic regulation. Methods: We have included 29 patients with HF who underwent cardiac surgery and were followed up for 5 years. Released proteins by epicardial adipose tissue (EAT) after isoproterenol treatment were identified by nano-high-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…By contrast, in HFrEF, this increased activity might increase total catecholamine accumulation in the myocardium and worsen systolic performance. A biopsy study in patients with heart failure showed that, after treatment with isoprenaline (an agonist of the catecholaminergic β-adrenergic receptor), EAT releases molecules involved in the inflammatory response or extracellular matrix 117 . Interestingly, EAT expression of CD5L, a macrophage apoptosis inhibitor stimulated by isoprenaline, was higher in patients with heart failure who developed atrial fibrillation during follow-up, although circulating levels of CD5L were not correlated with the risk of atrial fibrillation 118 .…”
Section: Role Of Eat In Cardiovascular Diseasementioning
confidence: 99%
“…By contrast, in HFrEF, this increased activity might increase total catecholamine accumulation in the myocardium and worsen systolic performance. A biopsy study in patients with heart failure showed that, after treatment with isoprenaline (an agonist of the catecholaminergic β-adrenergic receptor), EAT releases molecules involved in the inflammatory response or extracellular matrix 117 . Interestingly, EAT expression of CD5L, a macrophage apoptosis inhibitor stimulated by isoprenaline, was higher in patients with heart failure who developed atrial fibrillation during follow-up, although circulating levels of CD5L were not correlated with the risk of atrial fibrillation 118 .…”
Section: Role Of Eat In Cardiovascular Diseasementioning
confidence: 99%
“…In acute HF (AHF), exists a 20–30% of re-hospitalization within the first 3–6 months after discharge. It is coupled with an increase of acute-phase response reactants, measured by C-reactive protein (CRP) or interleukin-6 (IL-6) levels ( Goonewardena et al, 2016 ) and a raise of other several serum inflammatory cytokines levels such as tumor necrosis factor alfa (TNF-α) and interleukin-1b (IL-1β) which are associated with the degree of disease severity, poor outcomes, and mortality ( Goonewardena et al, 2016 ; Agra-Bermejo et al, 2020 ). A number of diagnostic and/or prognostic plasma biomarkers of worsening HF have been proposed during hospitalization and in chronic stable patients.…”
Section: Introductionmentioning
confidence: 99%
“…These findings led to the authors concluding that the inhibition of CD5L could prevent CVD in chronic inflammation and could attenuate the functional impairment after myocardial infarction [ 28 , 29 ]. In humans, higher CD5L concentrations on epicardial fat secretome were found in male subjects with heart failure who developed atrial fibrillation [ 30 ]. Those results also support the hypothesis that CD5L could be useful for predicting CVD.…”
Section: Discussionmentioning
confidence: 99%